Aggressive angiomyxoma of vagina mimicking genital prolapse: a case report and review of literature - Dahiya, Mona; Singhal, Chandra; Bansal, Satish; Jindal, Umesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Aggressive angimyxoma is a rare locally infiltrative mesenchymal neoplasm which arises in the pelvic and perineal regions of young women. It has a high rate of local recurrence because of infiltrative growth and anatomical location making complete excision with wide margins difficult. We present a rare case of a young woman who came with history of something coming out per vaginum. Clinical examination and imaging studies revealed an elongated mass arising from the anterior vaginal wall protruding outside the introitus .A diagnostic biopsy revealed provisional diagnosis of spindle cell tumour. Enucleation of the mass was done and the histopathology report confirmed the diagnosis of aggressive angimyxoma. It was concluded that, Aggressive angiomyxoma is a rare benign, site specific, hormone dependant mesenchymal tumour occurring in young females. It is a masquerader and should be distinguished from other benign conditions. The case is presented for its rarity and stressing the need for a high index of suspicion in diagnosing differentials of vaginal and vulval mass. Long term follows up and careful monitoring is necessary to rule out the possibility of recurrence.